2018
DOI: 10.1074/jbc.ra117.001042
|View full text |Cite
|
Sign up to set email alerts
|

An essential thioredoxin is involved in the control of the cell cycle in the bacterium Caulobacter crescentus

Abstract: Thioredoxins (Trxs) are antioxidant proteins that are conserved among all species. These proteins have been extensively studied and perform reducing reactions on a broad range of substrates. Here, we identified Caulobacter crescentus Trx1 (CCNA_03653; CcTrx1) as an oxidoreductase that is involved in the cell cycle progression of this model bacterium and is required to sustain life. Intriguingly, the abundance of CcTrx1 varies throughout the C. crescentus cell cycle: while the expression of CcTrx1 is induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…5f ). Finally, overexpression of Cc CnoX suppressed the essentiality of Cc Trx1 ( Table 1 ), a C. crescentus Trx protein with a WCGPC motif that we recently characterized as essential ( 31 ) (see Discussion). In combination, these results reveal that Cc CnoX is a real Trx oxidoreductase that functions in a classical reducing pathway.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…5f ). Finally, overexpression of Cc CnoX suppressed the essentiality of Cc Trx1 ( Table 1 ), a C. crescentus Trx protein with a WCGPC motif that we recently characterized as essential ( 31 ) (see Discussion). In combination, these results reveal that Cc CnoX is a real Trx oxidoreductase that functions in a classical reducing pathway.…”
Section: Resultsmentioning
confidence: 87%
“…The identification of 90 redox substrates of Cc CnoX ( Table S1 ) agrees with this idea. We previously reported that Cc Trx1, the only single-domain Trx expressed by C. crescentus , is essential—probably because it is responsible for the recycling of ribonucleotide reductase ( 31 ), the essential enzyme that catalyzes the reduction of ribonucleotides to their corresponding deoxyribonucleotides ( 36 ). Since Cc CnoX does not rescue the growth of the nonviable Δ Cctrx1 mutant unless overexpressed ( Table 1 ), the two proteins likely have different substrate specificities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, yeast DNA synthesis is temporally confined to the more reductive phase of the YMC 65 . Notably also, C. crescentus displays thioredoxin (Trx1) peak expression during S phase 66 and an overall redox shift during cell cycle progression 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NstA requires dimerization by formation of intermolecular cysteine disulfide bonds under oxidizing conditions in early S phase. Trx1 was recently reported to be specifically induced in early S phase to counteract oxidizing stress (Goemans et al, 2018). CcrM contains two conserved cysteines (C13 and C329), of which the latter is located in a motif that is critical for DNA binding activity.…”
Section: Discussionmentioning
confidence: 99%